EFFECT OF AN INTRAVITREAL DEXAMETHASONE IMPLANT ON DIABETIC MACULAR EDEMA AFTER CATARACT SURGERY - Calvo, Pilar (Retina, 2018)
PURPOSE: To analyze the effects of a dexamethasone intravitreal implant (DEX; Ozurdex 700 μg; Allergan) administered immediately after cataract surgery in diabetic patients. METHODS: This prospective, single-arm, open label study (NCT01748487 at ClinicalTrials.gov) involved Type 2 diabetic patients with at least mild diabetic retinopathy (DR) who underwent cataract surgery and DEX insertion after phacoemulsification, and intraocular lens implantation were enrolled. Best-corrected visual acuity and central retinal thickness (CRT) measured by spectral-domain optical coherence tomography were recorded at 1 week preoperatively, and 1 week, 1 month, and 3 months after surgery. Adverse events were also recorded. RESULTS: Twenty-four eyes of 24 patients (17 [70.8%] men; mean age 63.7 ± 8.7 years) with mild nonproliferative DR (41.7%), moderate nonproliferative DR (33.3%), severe nonproliferative DR (16.7%), or treated proliferative DR (8.3%) were selected. After DEX treatment, mean CRT changed from 241.1 μm (95% confidence interval, 227.5–254.6 μm) at baseline to 236.9 μm (95% confidence interval, 223.9–249.9 μm) at 1 week (P = 0.09), 238.9 μm (95% confidence interval, 225.5–252.3 μm) at 1 month (P = 0.44), and 248 μm (95% confidence interval, 232.4–260.8 μm) at 3 months (P = 0.15). No eyes showed a postoperative increase >50 μm in the CRT at any visit. A 10% increase in CRT was found in 8.3% of eyes. Mean best-corrected visual acuity significantly improved from 0.37 (20/50) at baseline to 0.19 (20/30) at 1 week, 0.12 (20/25) at 1 month, and 0.12 (20/25) at 3 months (P < 0.001 for each comparison). Mean intraocular pressure before surgery was 13.8 mmHg, and none of the patients developed an intraocular pressure ≥22 mmHg at any visit. None of the patients developed any serious adverse events during the follow-up. CONCLUSION: These short-term results suggest that a single DEX injection intraoperatively after phacoemulsification could avoid an increase in CRT after cataract surgery in diabetic patients.